PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KINERJA GURU DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING DI SMK NAHDLATUL ULAMA BALIKPAPAN - jurnalpps pps; Heri Santoso; Woro Utari; Indra Prasetyo (Jurnal Manajerial Bisnis, 2022)
This research aims to find out competence, and training of teacher performance with motivation as an intervening variable in the Nahdlatul Ulama Vocational School Modern Islamic Boarding School Foundation Al-Muttaqien. This research is a quantitative study, using multiple linear regression analysis. The number of research samples is the same as the research population of 30 teachers. This research was conducted from April 2020 - May 2020. The results of this study are the competency variables have a positive and significant influence on teacher motivation. With good competence in accordance with the workload, it can increase teacher motivation and get better. Competency variables, training variables, and motivation variables together have a positive and significant effect on teacher performance. The competency and training variables together have a positive and significant effect on teacher performance with motivation as an intervening variable. The training variable has a positive but not significant effect on teacher motivation.